Two new species and one new record of Hyalopsora (Pucciniastraceae) on ferns in China - Wang, Lei; Liu, Shi-Tong; Liu, Yun; Liang, Ying-Mei (Phytotaxa, 2021)
Three rust fungi belonging to the genus Hyalopsora occurring on ferns were found in China. Hyalopsora minispora and H. tibetica are described as new species in this paper. Hyalopsora minispora can be distinguished from known species by its relatively small urediniospores (19.5–23.0 × 12.0–19.0 μm) with 4–6 scattered germ pores and amphispores in a common pustule. Hyalopsora tibetica is mainly characterized by urediniospores with 2–6 scattered germ pores and amphispores. Hyalopsora neocheilanthis is described and reported as a new record for China. The phylogenetic relationships of Hyalopsora species and related taxa were examined by comparing the sequences of their internal transcribed spacer 2 (ITS2) barcode and 28S rDNA gene segments. Hyalopsora is supported with strong bootstrap support and it differs from the two other fern-infecting genera viz. Milesina and Uredinopsis.